Understanding Extraversion in Indonesian Adolescents: A Big Five Personality Analysis of High School Students in Surabaya - Rafiqoh, Syifa Ainur; Mauliyah, Hayyin Farihatul; Azizah, Nazalul Kharirotul; Kurniawati, Cindi; Budiani, Meita Santi (Universitas Muhammadiyah Surakarta, 2025)
Personality extraversion is an important aspect that influences the social development of adolescents, particularly high school students. While previous studies have highlighted extraversion in academic and social contexts, few have deeply examined how this dimension manifests in the social dynamics of students who are active in various social activities. This study aims to fill this gap by analyzing extraversion personality through six main aspects: affectionate, joiner, talkative, active, fun-loving, and passionate. Using a descriptive qualitative approach, four grade 11 students who are active in school organizations became the research subjects. Data were collected through semi-structured interviews and analyzed using thematic analysis techniques. The findings show that extraversion personality is not only related to the frequency of social interactions, but also the quality of interpersonal relationships as well as effectiveness in organizational activities. The novelty of this study lies in its contribution in expanding the landscape of adolescent personality studies with a focus on the context of intensive social participation and the balance between external needs and self-reflection. This study also offers practical contributions in the form of recommendations for educators and psychologists in designing social skills development programs as well as social exhaustion management strategies for extroverted individuals. The results of the study enrich the theoretical understanding of personality and can be the basis for the development of personality-based interventions in the school environment.